Control interno y su incidencia en los procesos contables de la Cooperativa de Consumo de Artículos de Primera Necesidad La Maná Ltda. del Cantón la Maná Provincia de Cotopaxi. - Chicaiza Ortega, Joyce Narcisa (2019)
The present investigation called: Internal control and its incidence on the accounting process of the Cooperative of Consumption of articles of first necessity “La Maná Ltda.” of Canton La Maná, Province of Cotopaxi. It was carried out in the Cooperative of Consumption "La Maná Ltda." From the same Canton, due to the need to know the impact of internal control within the accounting process. The general objective of this project is to determine the incidence of internal control over the accounting processes in the cooperative. For this purpose, we used a type of descriptive documentary bibliographic research, supported with techniques and information-gathering tools such as the interview, applied to the secretary and legal representative of the institution, the survey, was applied to the partners, to obtain real information of the object of study; the sources of data collection were both primary and secondary, these were used for the elaboration of the theoretical framework, the tabulation of the information obtained through the surveys and analysis of the company's financial documents, an internal control questionnaire was also prepared to know the situation of the accounting area of the Cooperative, this allowed to draw conclusions and recommendations; for which it was possible to identify that the process carried out has some flaws in its application, based on this a proposal related to the research on a design of an internal control model based on the COSO I, which helps to improve and optimize the resources of the company through the accounting processes of the Consumer Cooperative, so that in this way the operation of this company helps to effectively disclose the real information of the financial situation.